The Influence of Recruitment Process, Performance Appraisal and Career Development on Expatriate Adaptation - A. Rahman, Fatmawati; Dorawati, Andi; Entong, Andi; Entong, Andi Ellyanti (PT Maju Malaqbi Makkarana, 2025)
This study aims to analyze the effect of human resource management functions, namely recruitment, performance appraisal, and career development, on expatriates' adjustment in the new work environment. In the context of increasing globalization, many companies send their employees to work abroad, making adaptation to new cultures and work systems crucial to their success. Qualitative research methods were used with in-depth interviews with an Indonesian expatriate working in Romania as a room attendant. The results showed that mental readiness and social support from local coworkers play an important role in cultural, social, and occupational adjustment. Recruitment processes that consider the cultural readiness of potential expatriates have been shown to reduce the risk of adjustment failure, while structured performance appraisals provide constructive feedback to help expatriates understand company expectations. In addition, planned career development can improve expatriates' motivation and performance, although language barriers and less modern managerial systems in destination countries are major challenges in their career development. The conclusion of this study emphasizes the need for a holistic approach in supporting the success of the migrant workforce, including pre-departure training, continuous performance evaluation, and inclusive social support. Thus, companies are expected to design more effective strategies to facilitate expatriates' adjustment and improve their performance in the new work environment.